2014
DOI: 10.1074/jbc.m113.499194
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPase Arf6 Is Essential for the Tram/Trif Pathway in TLR4 Signaling

Abstract: Background:The small GTPase Arf6 affects LPS-induced cytokine secretion. Results: Arf6 regulates transport of the TLR4 adaptor protein Tram and internalization of LPS. Conclusion: Arf6 plays an essential role in regulating the Tram/Trif-dependent TLR4 pathway. Significance: Knowing how TLR4 is modulated is crucial for understanding innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 63 publications
2
36
1
Order By: Relevance
“…RAB11A GTPase is involved in the recruitment of TLR4 from the endocytic recycling compartment to E.coli phagosome (32) and affects localization of TICAM-2 to the endocytic recycling compartment and early sorting endosomes (32). The small GTPase ADP-ribosylation factor 6 also regulates transport of the TLR4 adaptor TIRAP and TICAM-2 to distinct signaling platforms (33). In addition, multiple molecules such as CD14, MD-2, PI3K, and Raftlin regulate TLR4 internalization (16,17,31), which is important in shifting the TLR4 signaling axis from MyD88 to TICAM-1, leading to expression of IFN-b and IFNstimulated genes including caspase 4/11, a cytoplasmic LPS receptor (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…RAB11A GTPase is involved in the recruitment of TLR4 from the endocytic recycling compartment to E.coli phagosome (32) and affects localization of TICAM-2 to the endocytic recycling compartment and early sorting endosomes (32). The small GTPase ADP-ribosylation factor 6 also regulates transport of the TLR4 adaptor TIRAP and TICAM-2 to distinct signaling platforms (33). In addition, multiple molecules such as CD14, MD-2, PI3K, and Raftlin regulate TLR4 internalization (16,17,31), which is important in shifting the TLR4 signaling axis from MyD88 to TICAM-1, leading to expression of IFN-b and IFNstimulated genes including caspase 4/11, a cytoplasmic LPS receptor (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, all of the evidence in animal models, including the present study, suggests that ARF6, while necessary for disease pathology, does not regulate cytokine release (15). In contrast, it has been proposed that inhibition of ARF6 in fibroblasts, macrophages, and dendritic cells decreases LPS-induced cytokine production by preventing the association of MYD88 with TIRAP and TLR4(41, 42). However, LTA-induced cytokine expression, which also requires the association of MYD88 to TIRAP, was not affected by ARF6 inhibition suggesting a greater complexity in these TLR-signaling pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific mechanism by which TLR4 is transported to the endosome was incompletely defined. The small GTPase ADP ribosylation factor 6 (ARF6) and Rab family of GTPases have been investigated in controlling endocytic transport of receptors (10). Recently, Husebye et al showed that Rab11a, a small GTPase, regulates recruitment of TLR4 and TRAM to E. coli phagosomes and controls both E. coli-and LPSinduced IRF3 activation (9).…”
Section: Cd14-independent Endocytosis Of Tlr4 In Macrophages Renderedmentioning
confidence: 99%